THE EFFECT OF OPERATING EFFICIENCY, CREDIT RISK, AND INTELLECTUAL CAPITAL ON COMPANY VALUE WITH MACROECONOMIC CONDITIONS AS MODERATING VARIABLE (An Empirical Study on Bank Sub-Sector of Indonesia Stock Exchange in the period of 2014-2018) - Jennah, Fadilatul (Jurnal Manajemen Update, 2021)
The important role of banking industry on the economy of a country raises the need for company valuation in this industry. In addition, company value is an aspect that investors pay attention to and it becomes the focus of the company because high company value reflects a fairly good state of the company and subsequently high shareholder welfare. This research attempted to investigate the effect of operating efficiency, credit risk, and intellectual capital on company value and macroeconomic conditions as moderating variable. The object in this research was the bank sub-sector listed on the Indonesia Stock Exchange in the period of 2014-2018. This research implemented quantitative and causal associative design with purposive sampling method obtaining 36 companies. Data analysis was performed using descriptive analysis, classic assumption test, and interaction effect test (moderated regression analysis). The test used the SPSS 20 program. The research results showed that operating efficiency had a significant positive effect on company value, credit risk had a significant negative effect on company value, intellectual capital had a significant positive effect on company value, and macroeconomic conditions were able to strengthen the effect of the three independent variables on company value.Keywords: operating efficiency, credit risk, intellectual capital, macroeconomic conditions, and company value DAFTAR PUSTAKAAgustiani, R. M. (2016). Pengaruh Good Corporate Governance, Return On Asset, Return On Equity, Bopo, Dan Capital Adequacy Ratio Terhadap Nilai Perusahaan Go Public Di Bursa Efek Indonesia. Jurnal Ekonomi Bisnis, Agustus 2016, Hal. 131-135, Vol. 21 Nomor 2. Diakses dari https://www.neliti.com/id/publications/178520/pengaruh-good-corporate-governance-return-on-asset-return-on-equity-bopo-dan-capAhmed, A., Khurshid, M. K., Yousaf, M. U. (2019). Impact of Intellectual Capital on Firm Value: The Moderating Role of Managerial Ownership. January 2019, 1-15. doi:10.20944/preprints201901.0318.v1.Arikunto, S. (2014). Prosedur Penelitian Suatu Pendekatan Praktik. Jakarta: Rineka Cipta.Bank Indonesia. (1998). UU No. 10 Tahun 1998, Tentang Perubahan Terhadap UU No. 7 Tahun 1992. Jakarta.Berzkalne, I., & Zelgalve, E. (2014). Intellectual Capital and Company Value. Procedia - Social and Behavioral Sciences 110, 2014, 887-896, ISSN 1877-0428. doi: 10.1016/j.sbspro.2013.12.934.Bhatnagar, D., Bhatnagar, C. S., & Bhullar, P. S. (2014). Operating Efficiency and Firm Valuation: Evidence from India. Industrial Engineering Letters, 2014, 45-54, ISSN 2224-6096 (Paper) ISSN 2225-0581 (online). Retrieved from https://www.researchgate.net/publication/274271563_Operating_efficiency_and_firm_valuation_evidence_from_IndiaBolasalju. (2019). Kinerja Indeks Harga Saham Gabungan 2010 2019. Diakses dari bolasalju.comDietrich, Andreas, & Wanzenried, G. (2009). What Determines the Profitability of Commercial Banks? New Evidence from switzerland. Diakses dari www.ssrn.comEbenezer, O. O., Islam, M. A., Junoh, M. Z. M., & Yusoff, W. S. (2019). Loan Growth, Bank Solvency and Firm Value: A Comparative Study of Nigerian and Malaysian Commercial Banks. Journal of Reviews on Global Economics, 2019, Hal. 373-386, Vol. 8, E-ISSN: 1929-7092. Retrieved from https://www.lifescienceglobal.com/pms/index.php/jrge/article/view/6002Frucot & Shearon. (1991). Uji Nilai Selisih Mutlak - Belajar SPSS. Diakses dari https://blogtutorialspss.blogspot.com/2012/06/uji-nilai-selisih-mutlak.htmlGhozali, Imam. (2012). Aplikasi Analisis Multivariate Dengan Program IBM SPSS 20. Semarang: Badan Penerbit Universitas Diponegoro.Gujarati. (2003). Ekonometri Dasar Terjemahan : Sumarno Zain. Jakarta: Erlangga.Halimah, S. N., & Komariah, E. (2017). Pengaruh ROA, HCAR, NPL, LDR, BOPO Terhadap Nilai Perusahaan Bank Umum. Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, Juli 2017, Hal. 14-25, Vol. 5 Nomor 1, E-ISSN: 2548-9836. Diakses dari https://pdfs.semanticscholar.org/7960/c95b5cda23923be 86153d807a758d7da1ef9.pdf.Hardanto. (2006). Makalah Manajemen Risiko Risiko Kredit. Diakses dari http://arinidwi99.blogspot.com/2017/07/makalah-manajemen-risiko-risiko-kredit.html.Hasibuan, S. P. (1984). Definisi / Pengertian Efisiensi. Diakses dari https://dansite.wordpress.com/2009/03/28/pengertian-efisiensi/.Ikhsan, A. (2008). Pengertian, Komponen Dan Pengukuran Intellectual Capital. Diakses dari https://www.kajianpustaka.com/2017/09/intellectual-capital.htmlLindenberg & Ross. (1981). Penyederhanaan TobinsQ. Diakses dari https://www.coursehero.com/file/p3h6mft/Mengingat-formula-diatas-memili ki-kelemahan-dalam-menentukan-market-value-of/Maimunah, S., & Fahtiani, T. (2019). Pengaruh NPL, ROA, DAN CAR Terhadap PBV Pada Bank BUMN. Jurnal Informasi Perpajakan, Akuntansi dan Keuangan Publik, Januari 2019, Hal. 19-36, Vol. 14 Nomor 1, ISSN : 2685-6441 (Online), ISSN : 1907-7769 (Print). doi : http://dx.doi.org/10.25105/jip ak.v14i1.5086Muhammad. (2011). Makalah Manajemen Risiko Risiko Kredit. Diakses dari http://arinidwi99.blogspot.com/2017/07/makalah-manajemen-risiko-risiko-kredit.html.Mulyamah. (1987). Definisi / Pengertian Efisiensi. Diakses dari https://dansite.wordpress.com/2009/03/28/pengertian-efisiensi/.Nazir, M. (1998). Studi Kepustakaan. Diakses dari http://phairha.blogspot.com/2012/ studi-kepustakaan.html.Noerirawan. (2012). Pengertian, Jenis, dan Pengukuran Nilai Perusahaan. Diakses https://www.kajianpustaka.com/2017/11/pengertian-jenis-dan-pengukuran-nilai-perusahaan.html.Nunki, D. C., Sudibya, A., & Restuti, MI. M. D., (2014). Pengaruh Modal Intelektual Terhadap Nilai Perusahaan Dengan Kinerja Keuangan Sebagai Variabel Intervening. BENEFIT Jurnal Manajemen dan Bisnis, Juni 2014, Hal. 14 29, Vol. 18 Nomor 1. Diakses dari http://journals.ums.ac. id/index.php/ benefit/article/view/1390.Otoritas Jasa Keuangan (2019). Statistik Perbankan Indonesia Desember 2019. Jakarta: OJKPangestika. (2010). Pengertian, Komponen Dan Pengukuran Intellectual Capital. Diakses dari https://www.kajianpustaka.com/2017/09/intellectual-capital.htmlPulic, A. (1998). Measuring the performance of intellectual potential in knowledge economy, paper presented at the 2nd McMaster World Congress on Measuring and Managing Intellectual Capital. Canada: Hamilton.Randa, F., & Solon, S. A. (2012). Pengaruh Modal Intelektual Terhadap Nilai Perusahaan (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia). Jurnal Sistem Informasi Manajemen dan Akuntansi, April 2012, Hal. 24 47, Vol. 10 No. 1. Diakses dari https://www.academia.edu/4408830/PENGARUH_MODAL_INTELEKTUAL_TERHADAP_NILAI_PERUSAHAAN_Studi_Empiris_pada_Perusahaan_Manufaktur_yang_Terdaftar_di_Bursa_Efek_Indonesia_-genap_2011_2012Repi, S., Murni, S., & Adare, D. (2016). Faktor-Faktor Yang Mempengaruhi Nilai Perusahaan Subsektor Perbankan Pada BEI Dalam Menghadapi MEA. Jurnal EMBA, Maret 2016, Hal. 181-191, Vol. 4 Nomor 1, ISSN 2303-1174. Diakses dari https://ejournal.unsrat.ac.id/index.php/emba/article/view/11585Samuelson & Nordhaus. (2010). Pengertian Ekonomi Makro Menurut Para Ahli. Diakses dari https://kotakpintar.com/pengertian-ekonomi-makro-menurut-para-ahli/Sartono. (2010). Pengertian, Jenis, dan Pengukuran Nilai Perusahaan. Diakses dari https://www.kajianpustaka.com/2017/11/pengertian-jenis-dan-pengukuran-nilai-perusahaan.html.Sastradipoera. (2001). Makalah Manajemen Risiko Risiko Kredit. Diakses dari http://arinidwi99.blogspot.com/2017/07/makalah-manajemen-risiko-risiko-kredit.html.Sekaran, U. (2017). Metode Penelitian Untuk Bisnis Pendekatan Pengembangan Keahlian. Jakarta: Salemba Empat.Sirojudin, G. A., & Nazaruddin, I. (2014). Pengaruh Modal Intelektual dan Pengungkapannya Terhadap Nilai dan Kinerja Perusahaan. Jurnal Akuntansi & Investasi, Juli 2014, Hal. 77-89, Vol. 15 No. 2. Diakses dari https://journal.umy.ac.id/index.php/ai/article/view/1328Streiner. (2005). Mengenal Path Analysis Sejarah. Diakses dari https://media.neliti.com/media/publications/98454-ID-mengenal-path-analysis-sejarah-pengertia.pdfSugiyono. (2017). Metode Penelitian Kuantitatif, Kualitatif, dan R&D. Bandung: Alfabeta.Sukirno, S. (2000). Pengertian Ekonomi Makro Menurut Para Ahli. Diakses dari https://kotakpintar.com/pengertian-ekonomi-makro-menurut-para-ahli/Tobin, J. (1968). Pitfalls in Financial Model-Building. Diakses dari https://ideas.repec.org/e/pto4.htmlhttp://www.bi.go.id/http://www.finance.yahoo.com/http://www.ojk.go.id/